A Novel Regulator of Activation-Induced Cytidine Deaminase/APOBECs in Immunity and Cancer: Schrödinger’s CATalytic Pocket - King, Justin J.; Larijani, Mani (Frontiers in Immunology, 2017)
Abstract Activation-induced cytidine deaminase (AID) and its relative APOBEC cytidine deaminases boost immune response by mutating immune or viral genes. Because of their genome-mutating activities, AID/APOBECs are also drivers of tumorigenesis. Due to highly charged surfaces, extensive non-specific protein-protein/nucleic acid interactions, and general insolubility, structure elucidation of these proteins in their native forms by X-ray crystallography and NMR has been challenging. Hence, almost all available APOBEC structures are of mutated and/or truncated versions. Since AID’s discovery two decades ago, its native structure had eluded X-ray or NMR solution. Last year, a functional structure for AID was reported using a combined computational-biochemical approach. In so doing, a novel regulatory mechanism in human DNA/RNA-editing enzymes came to light, through frequent catalytic pocket closure. Recent X-ray and NMR studies have shown that multiple other APOBECs also close their catalytic pockets. Here, we highlight catalytic pocket closure as an emerging and important regulatory mechanism of AID/APOBECS. We focus our review on three sub-topics: first, we propose that variable pocket closure rates across AID/APOBECs underlie differential activity in immunity and cancer and review the supporting evidence for this suggestion. Second, we discuss pocket closure as an ever-present internal regulator, in the context of other proposed regulatory mechanisms that involve extrinsic binding partners. Third, we discuss the utility of various methodological approaches for ability to observe dynamic regulatory features like pocket closure, and relate these to biological functions.